Line following robot using MC68HC11 - Mohd Anwar, Jahrani (2009)
In the industry, carriers are required to carry products from one manufacturing plant to another which are usually in different buildings or separate blocks. Conventionally, carts or trucks were used with human drivers. Unreliability and inefficiency in this part of the assembly line formed the weakest link. The project is to automate this sector, using carts to follow a line instead of laying railway tracks which are both costly and an inconvenience. This project using MC68HC11 as a main component to build a line following robot that can follow a single line which is can solve that entire problem. Motor control was performing with servo-motor and all the wiring was done using wire wrap. Line following robot can be easily design by using concept on and off but this type of design will make robot follow a line smoothly and sometimes robot tends to move out of track. To overcome this problem we try to using more sensors to get an accuracy input.